Recruitment System Analysis in Improving Employee Performance Using Relevant Marketing Strategies at the Al Sudais Indonesia Foundation - Zulhamsyah, Ahmad; Suryani Pratiwi, Bening; Hamid Al Farizin, Abdul; Ramadhan, Syahrul (Lafadz Jaya Publisher, 2024)
Human resources are an important aspect of competitive advantage in an organization with the overall value of its capabilities, knowledge, skills, experience, and motivation. To build and improve the quality of its human resources, the company implements human resource management. One of the activities in human resource management is planning and procuring human resources for an organization that suits its needs. Efforts to fulfill these needs can be made through a recruitment process. The purpose of this research is to determine the implementation of the recruitment system at the Al Sudais Indonesia Foundation. This type of research is research with descriptive qualitative methods. The results of this research reveal that the Al Sudais Indonesia Foundation has implemented a needs-based recruitment system. Starting from analyzing the employee needs of each division, determining the qualifications of prospective employees, carrying out the recruitment process both internally and externally, carrying out the selection process for both files and technical abilities, ending with checking the background of job applicants.